Ecophysiological Responses of Tall Wheatgrass Germplasm to Drought and Salinity - Borrajo, Celina Ines; Sánchez‐Moreiras, Adela M.; Reigosa, Manuel J. (MDPI, 2022)
Tall wheatgrass (Thinopyrum ponticum (Podp.) Barkworth and D.R. Dewey) is an important, highly salt-tolerant C3 forage grass. The objective of this work was to learn about the ecophysiological responses of accessions from different environmental origins under drought and salinity conditions, to provide information for selecting superior germplasm under combined stress in tall wheatgrass. Four accessions (P3, P4, P5, P9) were irrigated using combinations of three salinity levels (0, 0.1, 0.3 M NaCl) and three drought levels (100%, 50%, 30% water capacity) over 90 days in a greenhouse. The control treatment showed the highest total biomass, but water-use efficiency (WUE), δ13C, proline, N concentration, leaf length, and tiller density were higher under moderate drought or/and salinity stress than under control conditions. In tall wheatgrass, K+ functions as an osmoregulator under drought, attenuated by salinity, and Na+ and Cl− function as osmoregulators under salinity and drought, while proline is an osmoprotector under both stresses. P3 and P9, from environments with mild/moderate stress, prioritized reproductive development, with high evapotranspiration and the lowest WUE and δ13C values. P4 and P5, from more stressful environments, prioritized vegetative development through tillering, showing the lowest evapotranspiration, the highest δ13C values, and different mechanisms for limiting transpiration. The δ13C value, leaf biomass, tiller density, and leaf length had high broad-sense heritability (H2), while the Na+/K+ ratio had medium H2. In conclusion, the combined use of the δ13C value, Na+/K+ ratio, and canopy structural variables can help identify accessions that are well-adapted to drought and salinity, also considering the desirable plant characteristics. Tall wheatgrass stress tolerance could be used to expand forage production under a changing climate.